(3SdhI GdCMRGf aj CTYGQ GdfShGfs - (3ChMO Hf eMeO Hf LeGd GdChMOj GdHdjGfjs
(3ChdgG (B:s
(3hHYO Efi efP JMdjJ HGdTYhQ JeScJ HCQOGf GdCOH agLjS ai NGWQi Cf CLeY UMjaI JMJhdi Ydi JQGLe WGFaI ef GdfShGf GdThGYQ MJi SGYOfi GdReGf HJCdjagG s
(3BNQgG (B:s
(3gPG BNQ eG eL Gdbde ef GdShGO Ydi GdHjGV , hCJi HeG jZfi GdfhGXQ Yf GdfXQ ai GdQjGV s
(3gfGc Tc ai Cf GdeDda gh fGSN GdeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B232 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJGQjNs